Design and Simulation of a 19-Electrode MEMS Piezoelectric Thin-Film Micro-Deformable Mirror for Ophthalmology - Yisen Hu; Hongbo Yin; Maoying Li; Tianyu Bai; Liang He; Zhimin Hu; Yuanlin Xia; Zhuqing Wang (Micromachines, 2024)
This study presents a numerical simulation-based investigation of a MEMS (micro-electromechanical systems)technology-based deformable mirror employing a piezoelectric film for fundus examination in adaptive optics. Compared to the classical equal-area electrode arrangement model, we optimize the electrode array for higher-order aberrations. The optimized model centralizes electrodes around the mirror center, which realizes low-voltage driving with high-accuracy correction. The optimized models exhibited commendable correction abilities, achieving a unidirectional displacement of 5.74 μm with a driven voltage of 15 V. The voltage–displacement relationship demonstrated high linearity at 0.99. Furthermore, the deformable mirror’s influence matrix was computed, aligning with the Zernike standard surface shape of the order 1–3. To quantify aberration correction capabilities, fitting residuals for both models were calculated. The results indicate an average removal of 96.8% of aberrations to the human eye. This underscores that the optimized model outperforms the classical model in correcting high-order aberrations.